2005
DOI: 10.1111/j.1469-7610.2004.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediating links between maternal depression and offspring psychopathology: the importance of independent data

Abstract: Results emphasize the importance of independent data for testing mediational claims, and support claims that the processes involved in the intergenerational transmission of psychopathology are different for male and female youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
4
17

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 43 publications
10
107
4
17
Order By: Relevance
“…Some studies have reported that girls are particularly susceptible to negative effects of parental depression (Burt et al, 2005;Fergusson, Horwood, & Lynskey, 1995;Davies & Windle, 1997), whereas some other studies have found that boys are more susceptible to negative effects of parental depression than girls are (Carter et al, 2001;Essex, Klein, Cho, & Kraemer, 2003;Weinberg et al, 2006). There are also studies which have not found gender differences at all (for a review, see Gartstein et al, 2009;Goodman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have reported that girls are particularly susceptible to negative effects of parental depression (Burt et al, 2005;Fergusson, Horwood, & Lynskey, 1995;Davies & Windle, 1997), whereas some other studies have found that boys are more susceptible to negative effects of parental depression than girls are (Carter et al, 2001;Essex, Klein, Cho, & Kraemer, 2003;Weinberg et al, 2006). There are also studies which have not found gender differences at all (for a review, see Gartstein et al, 2009;Goodman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In general, mothers' depression (for a review, see Connell & Goodman, 2002) and depressive symptoms (Durbin, Klein, Hayden, Buckley, & Moerk, 2005) seem to be more strongly associated with child distress than those of fathers. Results concerning the role of child's gender, in turn, have been inconsistent: some studies have found that females are more susceptible to the negative effects of parental depression than males are (e.g., Burt et al, 2005;Fergusson, Horwood, & Lynskey, 1995;Davies & Windle, 1997), whereas some other studies have found that the effects are stronger for boys than girls, particularly among younger children (Carter, Garrity-Rokous, Chazan-Cohen, Little, & Briggs-Gowan, 2001;Weinberg, Olson, Beeghly, & Tronick, 2006). There are still some other studies that have not found any gender differences (for a review, see Gartstein, Bridgett, Dishion, & Kaufman, 2009;Goodman, Rouse, Connell, Broth, Hall, & Heyward, 2011).…”
Section: Parental Affection and Psychological Control As Mediators Bementioning
confidence: 99%
See 1 more Smart Citation
“…De acordo com a Tabela 3, pode-se observar que todos os 11 estudos avaliaram a fase escolar e incluíram, além desta, a fase pré-escolar ou a adolescência, com destaque para três artigos 16,33,34 que abrangeram desde a pré-escola até a adolescência. As variáveis abordadas para as crianças foram psicopatologia e problemas de comportamento, sendo que três estudos 26,33,34 analisaram tanto comportamentos internalizantes quanto externalizantes.…”
Section: Fase Dounclassified
“…As variáveis abordadas para as crianças foram psicopatologia e problemas de comportamento, sendo que três estudos 26,33,34 analisaram tanto comportamentos internalizantes quanto externalizantes.…”
Section: Fase Dounclassified